PENGARUH ENTREPRENEURSHIP ORIENTATION DAN MARKETING ORIENTATION TERHADAP FIRM PERFORMANCE DENGAN INOVASI SEBAGAI VARIABEL MODERASI: (Studi Penelitian pada Pelaku UMKM di Malang Raya) - Wi Endang Nirowati Pamungkas, Maria Goretti (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2024)
The Influence of Entrepreneurship Orientation and Marketing Orientation on Firm Performance with Innovation as a Moderating Variable (Research Study on MSME Players in Malang Raya). Problems faced by MSMEs include the quality of human resources, obstacles in accessing capital and funding, lack of knowledge in relationships with customers, the creation of new markets and sources of innovation. The novelty of this research is that it accommodates the Innovation variable as a moderating variable. In 2024, the largest number of MSMEs throughout Indonesia will be in East Java at 1,153,576 units and Malang City will have approximately 8,000 MSMEs. Research objectives can contribute both theoretically and managerially. The research methodology uses Partial Least Squares (PLS) analysis as a testing tool with Warp-PLS statistics. R-Square Firm Performance of 0.578 shows the contribution of Innovation to Firm Performance of 57.8%, while the remaining 42.2% is the contribution of other variables not discussed in this research. Q-Square Firm Performance is 0.575, which shows that the Innovation variable has strong predictive power on Firm Performance. The P-Value value from direct hypothesis testing is <0.001 and indirect testing <0.001, indicating that there is a significant influence of Entrepreneurship Orientation and Marketing Orientation on Innovation and Firm Performance. Indirect testing of <0.001 shows that there is a significant influence of Entrepreneurship Orientation and Marketing Orientation on Firm Performance with Innovation moderating.